2020
DOI: 10.1108/jima-01-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

The branding of religious financial institutions in the UK: conversations with market actors within the Islamic financial sector

Abstract: Purpose We are beginning to observe the growth of Islamic finance beyond the borders of traditionally Islamic markets such as the Middle East and the Far East. The proliferation of such religious financial institutions in non-Islamic and more secular markets has raised some pertinent questions about how these quasi-religious institutions brand themselves in light of the need to balance the conflation of Islamic theology with that of financial economic principles. Design/methodology/approach The study adopts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Hence, business and religion are unity with regard to which products and services are authorized and which are prohibited (Amin, 2020). Muslims have adopted these principles to adopt Islamic bank products and services (Junaidi et al , 2021; Kok, 2021; Zainudin et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, business and religion are unity with regard to which products and services are authorized and which are prohibited (Amin, 2020). Muslims have adopted these principles to adopt Islamic bank products and services (Junaidi et al , 2021; Kok, 2021; Zainudin et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Junaidi et al (2021) concluded that religiosity also positively affects consumers' commitment and materialism in Indonesia. Religiosity also has a crucial role in influencing brand image in Saudi Arabia (Abalkhail, 2021), the UK (Kok, 2021) and the USA (Liu and Minton, 2018). Unfortunately, the authors avoided simultaneously validating the role of materialism and Islamic brand image among Muslims in conventional and Islamic bank contexts.…”
Section: Introductionmentioning
confidence: 99%